Eye‐Readable Detection and Oxidation of CO with a Platinum‐Based Catalyst and a Binuclear Rhodium Complex. Issue 35 (22nd July 2019) - Qu, Jiafu; Cao, Yueqiang; Duan, Xuezhi; Li, Najun; Xu, Qingfeng; Li, Hua; He, Jinghui; Chen, Dongyun; Lu, Jianmei
Abstract: Toxic gases that are colorless and odorless, such as CO, are a major environmental concern and require early detection to prevent serious toxicological effects. In this study, a unique system (Pt/HMSs‐BRC) was fabricated by combining a catalyst (Pt/hollow mesoporous silica spheres, Pt/HMSs) with a silica gel containing an adsorbed chromogenic probe (binuclear rhodium complex, BRC). The process is a simple method to prepare well‐dispersed and uniform Pt nanoparticles. The Pt/HMSs‐BRC materials demonstrated early CO detection and excellent catalytic performance for CO oxidation. The probe exhibited remarkable color modulation from gray‐violet to light‐yellow when exposed to CO concentration levels above 50 ppm, and the color of the chromogenic probe was fully recoverable. By a kinetics‐assisted discrimination method and DFT calculations, it was found that the corner Pt sites are the dominant active sites for CO oxidation. Abstract : Now you see it, now you don't : A chromogenic probe was adsorbed onto silica gel and combined with a Pt catalyst supported on hollow mesoporous silica spheres (HMSs) for the simultaneous detection and catalytic conversion of CO (see picture). The Pt/HMSs catalyst was able to convert 100 % of the CO, and the chromogenic probe displayed a remarkable color change at CO concentration levels above 50 ppm.